A SIMSCAPE based design of a dual maximum power point tracker of a stand-alone photovoltaic system - Mohammed S. Ibbini; Abdullah H. Adawi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper presents the simulation of a dual maximum power point tracker (dual-MPPT) and attempt to get the global maximum power point GMPP under partial shading conditions for a solar photovoltaic module using MATLAB SIMSCAPE. Traditional single MPP trackers are less efficient than dual MPP trackers and have greater sensitivity to partial shading. By using dual MPP trackers, one can get several features such as the possibility of connecting two arrays with different string sizes or different solar azimuths or tilts within high efficiency. This paper focuses on making the photovoltaic system work at maximum possible power under partial shading condition by using dual MPP trackers to achieve the convergence toward the global maximum power point GMPP.